Pengaruh Fashion Influencer Terhadap Warna Busana Generasi Z - Monica Ester; Anna Amalyah Agus (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Color selection is an important aspect when it comes to purchasing clothes, but there are not many studies linking color in fashion and marketing science. This study analyzes the influencer's attributes on the perceived character of followers so the creation of perceived customer value is established to find purchase intentions, and clothing color preferences in Indonesian’s Generation Z. With a sample size of 388 respondents, the researchers utilized a quantitative descriptive strategy to gather primary data by having survey participants fill out questionnaires. The Structural Equation Model (SEM) approach would then be used to examine the data that was gathered. The results prove that not all variables positively influence purchase intention in clothing color preference and the most desirable clothing colors is pink, blue, and yellow. In order to avoid product waste and improve marketing effectiveness, marketing professionals can use this research as a useful resource when choosing the color of apparel to be produced. Keywords: fashion color, generation Z, influencer marketing, purchase intention, social media